HEROISM IN DANIELLE STEEL’S WINNERS - Gongsar Silaban (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2018)
This study deals with Heroism in Danielle Steel’s Winners.The problems of this study arerelated towhat characteristics of hero as portrayed by the main character in Danielle Steel’s Winners and how does the main character portray the characteristics of a hero in Danielle Steel’s Winners. The analyzing applies the theory of Rottman about characteristics of a hero; they are empathy, courage, sacrifice, responsibility, selflessness, humility, determination, and wisdom. The method used by the writer in analyzing heroism of the main character in novel is descriptive qualitative method. The findings about heroism shown in Winners such as empathy, courage, sacrifice, responsibility, selflessness, humility, determination, wisdom and the ways of main character as true hero and a good father who always sacrifices to save life of his only daughter.